2016
DOI: 10.1007/s10067-016-3168-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of different supplementation on oxidative status in patients with rheumatoid arthritis

Abstract: Rheumatoid arthritis is a chronic inflammatory disease. Reactive oxygen species have been considered as aggravating factors for autoimmune diseases. Fatty acids had been linked in reduction of various diseases by augment of their antioxidant potential and antiinflammatory mechanisms. The aim of this study was to assess the oxidative status in patients with rheumatoid arthritis who used concentrated fish oil only or concentrated fish oil in combination with evening primrose oil in a period of 3 months. Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In the present study, we observed increased ROS and TBARS levels in the untreated arthritic group, which may be owing to the production of ROS as a result of inflammation, leading to the destruction of cartilage and bone, neutrophil degranulation, and the release of various potentially harmful enzymes . Oxidative stress can induce the peroxidation of membrane lipids, which may result in inactivation of membrane‐bound receptors or enzymes with a consequential increase in tissue permeability and damage to normal cellular function .…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…In the present study, we observed increased ROS and TBARS levels in the untreated arthritic group, which may be owing to the production of ROS as a result of inflammation, leading to the destruction of cartilage and bone, neutrophil degranulation, and the release of various potentially harmful enzymes . Oxidative stress can induce the peroxidation of membrane lipids, which may result in inactivation of membrane‐bound receptors or enzymes with a consequential increase in tissue permeability and damage to normal cellular function .…”
Section: Discussionmentioning
confidence: 47%
“…The endogenous antioxidant defenses counteract the damage caused by oxidative stress and are divided into enzymatic and nonenzymatic. Enzymatic antioxidant defenses are composed of catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase, while nonenzymatic systems comprise substances such as vitamin C, vitamin E, carotenoids, and flavonoids …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the possible onset of lipid peroxidation and its relevance to the pathophysiology of RA was estimated [37]. Recently, the oxidative stress status in RA patients, supplemented with fish oil and primrose oil, compared with control RA patients was investigated through the assessment of the free radical formation and the levels of antioxidants in human serum [19]. In the latter study, however, non-specific detection probes were used for monitoring hydrogen peroxide, superoxide anion and nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…By a broad definition, the antioxidant is any substance that, even if present at low concentrations, significantly prevents or delays the oxidation of its substrates [18]. In a recent study, the anti-inflammatory role of antioxidants, such as ascorbic acid and vitamin E, was addressed and the addition of such antioxidants to the treatment strategies has been strongly recommended for either the prevention or the treatment of the disease [19]. In addition, a randomized controlled study had investigated the dietary intervention in patients with RA and it was observed that the levels of ascorbic acid, uric acid and retinol in human plasma were inversely correlated with rheumatoid biomarkers, hence suggesting possible dietary antioxidant interventions in RA management [20].…”
Section: Introductionmentioning
confidence: 98%